The thyroid and glycaemic endocrine influences on brown adipose tissue and its measurement using infrared thermography - Law, James M. (2021)
Brown, and brown-like, adipose tissue provides a potential target for treatments to increase energy expenditure and the consumption of lipids and glucose. In humans, active depots have been shown to persist into adulthood where, previously, they were thought to atrophy in childhood. Due to the presence of uncoupling protein-1 (UCP1) within the inner mitochondrial membrane, brown adipocytes possess the capability to prevent the energy released during cellular respiration from being stored as adenosine triphosphate, instead allowing the energy to be released as heat. Since heat energy is, eventually, dissipated from the body, the result is energy expenditure. Why the body possesses such a tissue specifically designed to waste energy is explained by the benefit conferred by the ability to produce heat on demand, in response to cold challenge. The major alternative heat generating method, shivering, can respond instantly but produces vastly less heat for the same effort. Beyond the acute shivering response, which cannot be maintained for prolonged periods, brown adipose tissue is an essential contributor to thermal homeostasis.